SPATA2 links CYLD to the TNF‐α receptor signaling complex and modulates the receptor signaling outcomes. (15th June 2016) - Wagner, Sebastian A; Satpathy, Shankha; Beli, Petra; Choudhary, Chunaram
Abstract: TNF‐α is a key regulator of innate immune and proinflammatory responses. However, the composition of the TNF‐α receptor‐associated signaling complexes (TNF‐RSC) and the architecture of the downstream signaling networks are incompletely understood. We employed quantitative mass spectrometry to demonstrate that TNF‐α stimulation induces widespread protein phosphorylation and that the scope of phosphorylation expands in a temporal manner. TNF‐α stimulation also induces rapid ubiquitylation of components of the TNF‐RSC. Temporal analysis of the TNF‐RSC composition identified SPATA2 as a novel component of the TNF‐RSC. The predicted PUB domain in the N‐terminus of SPATA2 interacts with the USP domain of CYLD, whereas the C‐terminus of SPATA2 interacts with HOIP. SPATA2 is required for recruitment of CYLD to the TNF‐RSC. Downregulation of SPATA2 augments transcriptional activation of NF‐κB and inhibits TNF‐α‐induced necroptosis, pointing to an important function of SPATA2 in modulating the outcomes of TNF‐α signaling. Taken together, our study draws a detailed map of TNF‐α signaling, identifies SPATA2 as a novel component of TNF‐α signaling, and provides a rich resource for further functional investigations. Synopsis: Proteomic analysis identifies the global TNF‐α receptor interactome, including downstream phosphorylation and ubiquitylation events. SPATA2 is a component of the TNF receptor complex and is required to recruit the deubiquitylase CYLD and trigger TNF‐α‐induced necroptosis. Proteomic analyses provide a time‐resolved view of TNF‐α‐induced protein phosphorylation and ubiquitylation. Differential analysis upon TNF‐α induction identifies SPATA2 as novel agonist induced component of the receptor complex. SPATA2 binds CYLD and HOIP, and SPATA2 knockdown abolishes the TNF‐α‐dependent recruitment of CYLD. The PUB domain in the N‐terminus of SPATA2 interacts with the C‐terminal USP domain of CYLD. SPATA2 knockdown increases TNF‐α‐induced NF‐κB activation and impairs necroptosis. Abstract : Proteomic analysis identifies the global TNF‐α receptor interactome, including downstream phosphorylation and ubiquitylation events. SPATA2 is a component of the TNF receptor complex and is required to recruit the deubiquitylase CYLD.